Monocrotophos and Glyphosate: Are They Really Matter to Fish Health? - MOHAPATRA, S; SUNDARAY, J K; KUMAR, R; MISHRA, C S K (Journal of the Indian Society of Coastal Agricultural Research, 2021)
Fishes are the major group of vertebrates on the basis of their nutritive values and having importance in food chain. They are also a useful indicator of pollution. The consistent use of pesticides in modern agriculture has enhanced environmental risk worldwide. Indiscriminate uses of these pesticides contaminate the environment including the soil & water and might adversely affect the non-targeted organisms like fish. Monocrotophos (MCP) and glyphosate (GLY) are commonly used as insecticide and herbicide respectively, in agricultural fields to increase crop production. Runoff of these pesticides from the agricultural field may also affect the health of aquatic organisms especially fish. MCP is an acaricide of the vinyl phosphate group and its wide use provides many routes of entry into aquatic environments. GLY is broadly used to control unwanted weeds and grasses in agricultural, industrial, urban, forest and landscapes. Due to widespread use, these two agrochemicals have been usually detected in aquatic ecosystems representing a potential hazard to fish. Fish health depends on many parameters like growth, immune system, acetylcholinesterase activity, haematological parameter, reproduction, and endocrine system, etc. at different stages of life. This review aims to compile the toxic effects of these two agrochemicals on different life stages of many fish species.